Choroid plexus-derived extracellular vesicles exhibit brain targeting characteristics. (November 2022) - Pauwels, Marie J.; Xie, Junhua; Ceroi, Adam; Balusu, Sriram; Castelein, Jonas; Van Wonterghem, Elien; Van Imschoot, Griet; Ward, Andrew; Menheniott, Trevelyan R.; Gustafsson, Oskar; Combes, Francis; EL Andaloussi, Samir; et al.
Abstract: The brain is protected against invading organisms and other unwanted substances by tightly regulated barriers. However, these central nervous system (CNS) barriers impede the delivery of drugs into the brain via the blood circulation and are therefore considered major hurdles in the treatment of neurological disorders. Consequently, there is a high need for efficient delivery systems that are able to cross these strict barriers. While most research focuses on the blood-brain barrier (BBB), the design of drug delivery platforms that are able to cross the blood-cerebrospinal fluid (CSF) barrier, formed by a single layer of choroid plexus epithelial cells, remains a largely unexplored domain. The discovery that extracellular vesicles (EVs) make up a natural mechanism for information transfer between cells and across cell layers, has stimulated interest in their potential use as drug delivery platform. Here, we report that choroid plexus epithelial cell-derived EVs exhibit the capacity to home to the brain after peripheral administration. Moreover, these vesicles are able to functionally deliver cargo into the brain. Our findings underline the therapeutic potential of choroid plexus-derived EVs as a brain drug delivery vehicle via targeting of the blood-CSF interface. Graphical abstract: Image 1 Highlights: The blood-cerebrospinal fluid barrier, located at the choroid plexus, is a largely unexplored brain barrier in drug delivery. Extracellular vesicles hold great potential as drug delivery vehicle. Choroid plexus epithelial cell-derived extracellular vesicles home to the brain and choroid plexus. Choroid plexus epithelial cell-derived extracellular vesicles functionally deliver cargo to astrocytes and microglia.